Building Financial Awareness: Financial Literacy in the Era of Gen Z Materialism in Surabaya State University Environment - Reva Cahya Cantika Mariyono; Riza Yonisa Kurniawan (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study seeks to examine the connection between financial literacy and financial behaviour on students' materialism both directly and indirectly. Method: This research adopts an explanatory quantitative approach to determine the relationships between variables. A survey using questionnaires was conducted on economics students at the Faculty of Economics and Business, State University of Surabaya to obtain primary data. Data analysis was performed using SEM-PLS assisted by WarpPls software. Results: The research findings indicate a positive and significant effect between financial literacy and financial behaviour, but it does not have a significant impact on materialism. Financial behaviour has a negative and significant effect on materialism, while also successfully serving as a mediating variable. Novelty: The integration of financial literacy and financial behaviour to estimate materialism in a model, with a focus on economics students, represents the novelty of this research. The contribution of the study lies in encouraging policymakers and educational institutions to develop financial education curricula with a greater focus on practical applications rather than theory.